Effect of boron, molybdenum and zinc when applied as coatings on seeds of soybeans (Glycine max (L.) Merril) with respect to symbiotic nitrogen fixation - Ruschel, Alaides Puppim; Britto, Dirce P.P. de Souza; Carvalho, Luiz Ferreira de (Pesquisa Agropecuaria Brasileira, 2014)
Two greenhouse experiments were conducted to study the effects of minor elements and rhizobia inoculants when applied as coatings on seeds of soybeans, i.e. "pelleting". In the first experiment calcium carbonate, "fosforita" (rock phophate), calcium phosphate and calcium phosphate with minor elements (B, Mo, Mg), respectively, were applied in pellet coatings. These three coating treatments were compared with plants growing in soil treated with calcium carbonate and micro-nutrients (B, Mo, Mg) and plants grown on soil having no added minor elements, respectively. All treatments were studied with and without the use of Rhizobium inoculation. A second experiment compared pelleting with calcium carbonate, "fosforita" and a half-and-half mixture of "fosforita" and dolomitic limestone. Each of these 3 treatments were combined with the minor elements Boron, Molybdenum and Zinc in a 23 factorial. Both experiments were carried out on two soils, a Gray Hydromorphic soil of the "Ecologia" series and on a Red Yellow Podzolic of the "Itaguaí" series, both of which are represented at the IPEACS. In general terms, the present work showed that the seed coating treatments were effective in increasing nodulation and symbiotic nitrogen fixation. In terms of effect on nodulation, total nitrogen fixe I and dry weight of plants, "fosforita" was the better of the pellet treatments. The pellet treatment with calcium carbonate produced the higher content of nitrogen in the plants. Treatment effects obtained were greater on the "Ecologia" series than on the "ltaguaí" soil series. All seed coatings containing Molybdenum increased the nitrogen content of the plant through improved symbiotic fixation. When Molybdenum was applied in combination with "fosforita" the dry-weight of plants was increased.